1999
DOI: 10.1161/01.cir.100.14.1515
|View full text |Cite
|
Sign up to set email alerts
|

A Common Variant of the Endothelial Nitric Oxide Synthase (Glu 298 →Asp) Is a Major Risk Factor for Coronary Artery Disease in the UK

Abstract: Background-Endothelium-derived nitric oxide (NO) is synthesised from L-arginine by endothelial nitric oxide synthase (eNOS) encoded by the NOS 3 gene on chromosome 7. Because reduced NO synthesis has been implicated in the development of coronary atherosclerosis, which has a heritable component, we hypothesised that polymorphisms of NOS 3 might be associated with increased susceptibility to this disorder. Methods and Results-Single-strand conformation polymorphism analysis of NOS 3 identified a G3 T polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
340
8
22

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 491 publications
(396 citation statements)
references
References 30 publications
26
340
8
22
Order By: Relevance
“…9,12,13,23,26,34,35 The frequency of the T allele in Venezuelans was comparable to that described for Caucasians, since the T allele was found in 30% of the Venezuelan subjects studied (present study).…”
Section: Ethnicity and Enos Polymorphismssupporting
confidence: 87%
See 2 more Smart Citations
“…9,12,13,23,26,34,35 The frequency of the T allele in Venezuelans was comparable to that described for Caucasians, since the T allele was found in 30% of the Venezuelan subjects studied (present study).…”
Section: Ethnicity and Enos Polymorphismssupporting
confidence: 87%
“…48 Whereas in other studies, no association between 298Asp with coronary artery disease, [22][23][24][25] essential hypertension, [17][18][19][20][21] left ventricular hypertrophy and carotid atherosclerosis 17,35 and cerebrovascular disease 29,49 was observed.…”
Section: Ethnicity and Enos Polymorphismsmentioning
confidence: 90%
See 1 more Smart Citation
“…In this study we assessed IMT as an index of early atherosclerosis. There are several reports showing the association of Glu298Asp polymorphism and myocardial infarction [25,41,42]. On the other hand, there are inconsistencies according to European reports examining the association of Glu298Asp polymorphism and carotid atherosclerosis [43,44], and there has been no report about the association of -786T-C polymorphism and carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that this polymorphism is not silent and may possibly be perceived as a target for cleavage (Tesauro et al, 2000). Evidence has been presented that this polymorphism is associated with coronary spasm (Yoshimura et al, 1998), acute myocardial infarction, and coronary artery disease in Caucasians (Hingorani et al, 1999).…”
Section: Introductionmentioning
confidence: 99%